Qualitative features of psychological structure of the responsibility at the African and Latin American students - V A Timofejcheva (Peoples' Friendship University of Russia (RUDN University), 2009)
In clause qualitative features of structure of the responsibility at African and Latin American students are analyzed. Significant differences testify to specificity motivational, cognitive, productive, dynamic, emotional, strong willed displays of the responsibility which at the African students are more expressed.